2011
DOI: 10.1007/s10456-011-9242-0
|View full text |Cite
|
Sign up to set email alerts
|

Silencing TRPM7 mimics the effects of magnesium deficiency in human microvascular endothelial cells

Abstract: Evidence has accumulated to suggest that magnesium might play a role in controlling angiogenesis. Since microvascular endothelial cells are protagonists in this process, we investigated the behavior of these cells cultured in low extracellular magnesium or silenced for its transporter Transient Receptor Potential Melastatin (TRPM)7, essential for cellular magnesium homeostasis. In particular, we focused on some crucial steps of the angiogenic process, i.e. proliferation, migration, protease production and orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
76
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(83 citation statements)
references
References 39 publications
6
76
0
1
Order By: Relevance
“…TRPM7 might, therefore, act as "Mg 2+ -sensor" [323,326] . Consistently, silencing TRPM7 mimics the effect of lowering extracellular Mg 2+ in human microvascular ECs by impairing cell migration and arresting the cells in G0/G1 and G2/M phases [327] . Similarly, TRPM7 may inhibit EC proliferation via an extracellular signalregulated kinase (ERK)-dependent reduction in eNOS levels [328] .…”
Section: +mentioning
confidence: 56%
See 1 more Smart Citation
“…TRPM7 might, therefore, act as "Mg 2+ -sensor" [323,326] . Consistently, silencing TRPM7 mimics the effect of lowering extracellular Mg 2+ in human microvascular ECs by impairing cell migration and arresting the cells in G0/G1 and G2/M phases [327] . Similarly, TRPM7 may inhibit EC proliferation via an extracellular signalregulated kinase (ERK)-dependent reduction in eNOS levels [328] .…”
Section: +mentioning
confidence: 56%
“…Human umbilical vein ECs [325,327,328] +(RT-PCR, WB) -(RT-PCR) +(RT-PCR, WB) Mouse aortic ECs [329] +(RT-PCR, WB) +(RT-PCR) Human dermal microvascular ECs [327] +(RT-PCR, [8] +(RT-PCR, WB)…”
Section: (Rt-pcr) +/-(Rt-pcr) +(Wb) +(Rt-pcr) +(Rt-pcr) -(Rt-pcr) +(Rmentioning
confidence: 99%
“…Channel function for sustained phosphorylation of ERK1/2 is required for TRPM7-regulating cell behaviors (24,25). Meanwhile, extensive evidence has shown that ERK1/2 is significantly activated after various types of stimulation and subsequent cardiac fibrosis (26).…”
Section: Silencing Trpm7 and Ca 2+ Free Culture Impaired H 2 O 2 -Indmentioning
confidence: 99%
“…TRPM7 has been shown to be expressed in the human vascular system and to play a role in vascular functions (3,4,6,25,31,52,68,69,74,76). For example, in vascular smooth muscle cells, TRPM7 modulates Mg 2ϩ homeostasis (6,25).…”
mentioning
confidence: 99%